Ancient literature and philosophy of religion comparative research in the West's most sacred texts - Steele, Joel (Wipf & Stock, 2022)
"This work examines the parallels between ancient Ugaritic literature and the Old Testament. It demonstrates that human civilizations have certain generic cognitive similarities regarding the structuring of their societies--offering an alternative to the trendy composite or plagiaristic theory pertaining to Near Eastern literature and that of the Old Testament. Further, it may be deduced from these demonstrations that the Hebrew text has the ability, considering the vast number of resources within its own historiography, to be the primary source for determining clarification and accuracy. The second part of this study further critiques ideas regarding ancient literature and theology. It underscores the procedures, methods, and theories used to understand humanity's past from two philosophical perspectives--historical and theological. Moreover, it offers insights necessary for proper interpretation."-- $cProvided by publisher